Pre‐service teacher‐delivered behavioral skills training: A pyramidal training approach. (4th December 2019) - Andzik, Natalie R.; Schaefer, John M.
Abstract : This study evaluated the effectiveness of using a university‐based pyramidal approach (i.e., train the trainer) to teach four pre‐service teachers to train another person. These pre‐service teachers were taught to use behavioral skills training (BST) techniques to train other professionals to use an evidence‐based practice. Transfer to a generalization trainee was probed and three participants maintenance of BST fidelity was probed one year later, after the participants had begun teaching. Results indicate that the participants quickly acquired and maintained a high degree of fidelity with BST. Implications for research and practice are discussed.